Hunter Disease: A Case Report - Bajaj, N; Joshi, P; Bajaj, SK (Journal of Nepal Paediatric Society, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/jnps.v28i2.1389 J. Nepal Paediatr. Soc. Vol.28(2) 2008 p.62-65